Self Efficacy pada Guru Sekolah Dasar - Alawiyah, Ela Minchah Laila (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2017)
The teachers are one of the determinants it is success or failure on teaching and learning process in school. One of problematics that faced by teacher is the teacher lacks confidence in their own ability to overcome the problems. Based on the phenomenon, it is interest to conduct research on teacher’s self efficacy in elementary school. The method in this research is qualitative, while the data obtained through observation, interview, and as supporter used self efficacy scale of teacher. Subject in this study research amounted to 40 elementary school teachers in Sleman, Yogyakarta. Based on the result of observation, interview and self efficacy scale analysis on teacher, it can be concluded that there are 32,5% of teachers who have low self efficacy, 47,5% teachers who have moderate self efficacy, and 20% teachers who have high self efficacy. The result shows that there are teachers who still have low self efficacy, both at the time of teaching or in helping to solve students problems.